Geography and Morphology Affect the Ice Duration Dynamics of Northern Hemisphere Lakes Worldwide. Issue 12 (13th June 2020) - Warne, Connor P. K.; McCann, Kevin S.; Rooney, Neil; Cazelles, Kevin; Guzzo, Matthew M.
Abstract: Climate change continues to diminish ice cover duration for Northern Hemisphere lakes. However, the differential loss of lake ice duration for various types of lakes across the globe is not well established. In this study, we used time series of ice duration data (average length = 51 years) for 220 globally distributed Northern Hemisphere lakes to determine how local climate trends, geographical location, and physical properties of lakes affect their ice cover trends. Ice duration dynamics were influenced by surface air temperature trends, lake geography, and morphology. Deeper lakes, located at lower elevations, western longitudes, and lower latitudes, experienced the greatest reductions in ice cover over their time series. These results indicate that despite widespread patterns of warming, the individual features of lakes can determine how rapidly they are losing ice cover and may prove informative for future modeling and conservation efforts. Plain Language Summary: Citizen scientists and researchers alike have been visually logging the freezing and breakup dates of lake ice for hundreds of years. Studies have shown that lake ice duration (the number of days between freezing and breakup) has decreased over time due to human‐induced climate change. We have used this type of data to determine how the size and geographic location of a lake influence how its ice cover length in winter has changed over time. We found that deep lakes, at lower elevations, western longitudes, and lower latitudes, are losing ice cover at relatively fast rates. Our results demonstrate that even though warming is a general pattern on our planet, these specific types of lakes are being affected disproportionately, which may help to prioritize conservation efforts to preserve freshwater biodiversity and drinking water resources. Key Points: Lakes at lower elevations, western longitudes, and lower latitudes have been more affected by ice cover loss associated with global warming The rate of ice duration loss is also faster for deeper lakes